Smart-sustainability: A new urban fix?. (February 2019) - Martin, Christopher; Evans, James; Karvonen, Andrew; Paskaleva, Krassimira; Yang, Dujuan; Linjordet, Trond
Highlights: Urban policy positions smart urban development as a transformative approach to delivering sustainability. Transformative credentials of smartness is understood as a partial fix for economic, environmental and social urban challenges. Urban smart-sustainability fix concept focuses on how smart-sustainable city initiatives integrate digital and environmental agendas via entrepreneurial forms of urban governance. Three main dimensions constitute the urban smart-sustainability fix - spatial, digital, and collaborative. Urban smart-sustainability fix aims is to make the urban realm more manageable resulting in amplification, rather than transformation, of the dominant ecological modernisation agenda of sustainable development. Abstract: Urban policy increasingly positions smart urban development as a transformative approach to deliver sustainability. In this paper, we question the transformative credentials of smartness and argue that it is better understood as a partial fix for the economic, environmental and social challenges faced by cities. Drawing on the urban sustainability and smart city literatures, we develop the concept of the urban smart-sustainability fix. This concept focuses on how smart-sustainable city initiatives selectively integrate digital and environmental agendas via entrepreneurial forms of urban governance. We develop this concept by examining how the urban smart-sustainability fix is constructed in the European Commission's flagship smart cities and communities lighthouse projects, focusing on the Triangulum initiative. Our research reveals three elements of the urban smart-sustainability fix: (1) the spatial development of smart-sustainable districts; (2) the digitisation of urban infrastructure to reveal hidden processes; and, (3) collaborative experimentation with low-carbon and digital technologies. We argue that this has produced urban districts that are attempting to reduce their carbon emissions while promoting green economic growth. The main aim of the urban smart-sustainability fix is to make the urban realm more manageable resulting in amplification, rather than transformation, of the dominant ecological modernisation agenda of sustainable development.